A bio-based benzoxazine adhesive and its preparation method and application
By synthesizing low-temperature cured benzoxazine resins using isoligerine, and through photodimerization and thermal curing cross-linking reactions, the problems of high curing temperature and low bonding performance of benzoxazine resins in the prior art are solved, thereby achieving efficient bonding and thermal performance improvement.
Patent Information
- Application Number
- CN202411946129.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing biomass resin binders have problems with high curing temperature and low bonding properties, especially in the application of benzoxazine resins.
By using isoligerine as the phenol source, benzoxazine resin with low-temperature curing characteristics is synthesized, and a multi-crosslinked dense structure is formed through photodimerization and thermal curing cross-linking reactions, thereby improving the adhesive properties and thermal properties of the resin.
It significantly reduces the curing temperature of benzoxazine resin, improves its adhesive properties, thermal properties and mechanical properties, and has a simple synthesis process and is suitable for large-scale production.
Smart Images

Figure CN119351014B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of bio-based resin binders, and in particular relates to a bio-based benzoxazine adhesive and a preparation method and application thereof. Background Art
[0002] Benzoxazine resin is a new type of thermosetting material synthesized by selecting different types of phenol sources, amine sources, and formaldehyde as raw materials. Compared with traditional thermosetting resins, benzoxazine resin has attracted widespread attention because of its flexible structural controllability and can be endowed with a variety of excellent properties such as high flame retardancy, chemical resistance, low dielectric constant, and low water absorption. Currently, benzoxazine resin has been widely used in aerospace, hydrophobic flame retardants, antiseptic and antibacterial, and electronic communications as the main component of composite material matrix or adhesive.
[0003] In recent years, as people pay more and more attention to global resources and environmental issues, coupled with the large consumption of petrochemical resources for thermosetting resins, using bio-based resources instead of petroleum-based resources as raw materials to prepare new materials has become an effective way to achieve sustainable development. Establishing a sustainable low-carbon society, reducing the consumption of petrochemical resources, and developing bio-based high-performance resins that are both green and environmentally friendly have also become new hot spots for research and development by scientific researchers and the industrial community.
[0004] At present, biomass resin binders are developed based on phenolic resins, which must use formaldehyde as a raw material, resulting in the inevitable problem of formaldehyde release, and require multiple raw materials to be mixed and compounded, resulting in a complicated preparation process. Summary of the invention
[0005] Purpose of the invention: In order to solve the above technical problems, the present invention aims to provide a bio-based benzoxazine adhesive, which solves the technical problems of low bonding performance and high curing temperature of benzoxazine resin.
[0006] The present invention also provides a preparation method and application of a bio-based benzoxazine adhesive. By preparing the isoliquiritigenin bio-based benzoxazine resin adhesive, the curing temperature of the benzoxazine resin is greatly reduced, and at the same time, the bonding performance, thermal performance and mechanical properties of the resin are significantly improved through photodimerization and thermal curing.
[0007] The present invention uses chalcone bio-based isoliquiritigenin extracted from the Chinese medicinal material licorice as a phenol source. Not only is the raw material environmentally friendly, but isoliquiritigenin can also be used to synthesize a benzoxazine resin with low-temperature curing characteristics, and can form a multi-crosslinked dense structure after photodimerization and thermal curing to provide effective bonding force. At the same time, the resin monomer component can be used as an adhesive, and compared with other reported benzoxazine resins, it has the advantages of high bonding performance, low-temperature curing, and high-temperature resistance. In addition, its synthesis process is simple, efficient and high-yield, and has low equipment requirements, and is suitable for large-scale production.
[0008] Technical solution: In order to achieve the above-mentioned purpose, the present invention provides a bio-based benzoxazine adhesive, and the structure of the resin precursor benzoxazine monomer of the adhesive is as follows:
[0009] ,
[0010] Among them, the Select any one of the following structural fragments:
[0011] .
[0012] Preferably, the Selected from the following structural fragments:
[0013] .
[0014] The method for preparing the bio-based benzoxazine adhesive of the present invention comprises the following steps:
[0015] After mixing isoliquiritigenin, amine compounds and polyformaldehyde, an organic solvent is added, heated to react, and then the organic solvent is removed by rotary evaporation. After the reaction, the solid product is washed with water and dried to obtain a solid product based on isoliquiritigenin bio-based benzoxazine resin precursor, and then a polybenzoxazine resin adhesive is obtained by ultraviolet light dimerization and thermal curing cross-linking.
[0016] Furthermore, the amine compound has a structural formula of R-NH2, selected from any one of the following structural fragments:
[0017] .
[0018] Preferably, the amine compound has a structural formula of R-NH2, selected from the following structural fragments:
[0019] .
[0020] Furthermore, the molar ratio of isoliquiritigenin, amine compound and paraformaldehyde is 1:2:4-5.
[0021] Furthermore, the optimal molar ratio of isoliquiritigenin, amine compounds and paraformaldehyde is 1:2:4.4.
[0022] Furthermore, the reaction temperature is 80-120° C. and the reaction time is 8-18 hours.
[0023] Furthermore, the reaction temperature is preferably 100-120° C., and the reaction time is preferably 8-12 hours; if the reaction temperature is too high or the reaction time is too long, it is easy to cause the benzoxazine to open the ring, increase the by-products produced by the reaction, and affect the purity and yield of the product; on the contrary, the reaction cannot be fully closed, and the reaction is not sufficient, which not only affects the purity and yield of the product, but also increases the time cost.
[0024] Furthermore, the organic solvent is one of 1,4-dioxane, toluene and xylene, or a mixture of several of them.
[0025] Furthermore, the isoliquiritigenin-based benzoxazine resin precursor (benzoxazine monomer) can undergo photodimerization under 365 nm ultraviolet irradiation.
[0026] The bio-based benzoxazine adhesive of the present invention is used in aerospace, hydrophobic flame retardant, anticorrosion and antibacterial, and electronic communications.
[0027] The preparation method of the present invention adopts isoliquiritigenin. Since the structure of isoliquiritigenin contains a phenolic hydroxyl group protected by the keto group of the adjacent chalcone, the synthesized benzoxazine monomer can retain the phenolic hydroxyl structure, effectively improving the strength of its connection with the matrix while significantly reducing its curing temperature. In addition, the carbon-carbon double bond of the chalcone group in isoliquiritigenin can further increase the crosslinking density of benzoxazine through photodimerization and thermal curing crosslinking reaction, significantly improving the bonding efficiency. Since isoliquiritigenin is derived from biological raw materials, the development of this new bio-based benzoxazine resin is of great significance for new materials for sustainable development.
[0028] The present invention is directed to the technical problems such as low bonding performance and high curing temperature of benzoxazine resin. By molecular design, isoliquiritigenin is used. Since the structure of isoliquiritigenin contains a phenolic hydroxyl group protected by the keto group of an adjacent chalcone, the synthesized benzoxazine monomer can retain the phenolic hydroxyl structure, while effectively improving its connection strength with the matrix, significantly reducing its curing temperature. At the same time, the carbon-carbon double bond of the chalcone group in isoliquiritigenin can further improve the crosslinking density of benzoxazine by photodimerization and thermal curing crosslinking reaction, significantly improving bonding efficiency. The special molecule of the synthesized benzoxazine designed by the present invention improves its bonding performance by photodimerization, and its performance can be effectively enhanced under the condition of photodimerization.
[0029] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0030] The present invention uses the biomass material isoliquiritigenin as the raw material of the benzoxazine resin adhesive to synthesize a benzoxazine resin adhesive containing a phenolic hydroxyl group and a carbon-carbon double bond protected by the keto group of an adjacent chalcone, wherein the phenolic hydroxyl group can effectively improve the strength of the connection with the matrix while reducing the curing temperature, and the carbon-carbon double bond of the chalcone group in the isoliquiritigenin can form a photodimer containing a cyclobutane structure through 365nm ultraviolet irradiation, and further cross-linking is performed by thermal curing to improve the cross-linking density of the resin adhesive, so as to improve the bonding performance. The benzoxazine resin adhesive has a very low curing temperature and excellent bonding performance, thermal performance and mechanical properties, a peak curing temperature of 150-200°C, a bonding strength of more than 5Mpa, and a residual carbon rate of 70-80% at 800°C in an inert gas atmosphere.
[0031] The present invention has simple synthesis steps, high yield, low equipment requirements, and the cured benzoxazine resin has very excellent bonding properties, thermal and mechanical properties. The product components are single and do not need to be compounded, and no formaldehyde is released. The synthesis process is easy to implement and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The hydrogen nuclear magnetic resonance spectra of the precursor benzoxazine monomer and dimer obtained in Example 1;
[0033] Figure 2 The infrared spectra of the precursor benzoxazine monomer and dimer obtained in Example 1;
[0034] Figure 3 The DSC spectra of the samples obtained in Example 1 after direct thermal curing of the precursor benzoxazine monomer and after forming dimerization and thermal curing;
[0035] Figure 4 The TGA spectrum of the adhesive obtained by direct thermal curing of the benzoxazine monomer obtained in Example 1 and the formation of dimerization and thermal curing;
[0036] Figure 5 The bonding strength (tensile shear strength) test of the adhesive obtained in Example 1. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0038] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions specified in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0039] Example 1
[0040] Using p-methylaniline as the amine source; 2.56 g (0.01 mol) of isoliquiritigenin, 2.14 g (0.02 mol) of p-methylaniline, and 1.32 g (0.044 mol) of paraformaldehyde were added to a flask, and then 100 mL of toluene solution was added, and a condenser was connected, and stirred and reacted at 100°C for 10 h; after stopping the reaction, the organic solvent was removed by rotary evaporation, and then washed with water, and dried in a vacuum drying oven at 50°C for one day to obtain 5.11 g of benzoxazine monomer, with a yield of about 85%. The chemical reaction equation is as follows:
[0041] .
[0042] In this embodiment, the structure of the obtained precursor benzoxazine monomer product is:
[0043] .
[0044] The prepared benzoxazine monomer was irradiated with 10W 365 nm ultraviolet light for 30 minutes to form an ultraviolet dimer, and then heat-cured at 200°C for 2 hours to obtain a polybenzoxazine resin adhesive. The reaction formula of the heat-curing cross-linking is as follows:
[0045] ,
[0046] The nuclear magnetic resonance hydrogen spectrum, Fourier transform infrared spectrum and DSC curve of the benzoxazine monomer are as follows: Figure 1 , Figure 2 , Figure 3 As shown; the thermogravimetric curve and bonding strength test diagram of the polybenzoxazine resin adhesive obtained after cross-linking are as shown Figure 4 and Figure 5 shown.
[0047] Figure 1 The left figure is the H NMR spectrum of benzoxazine monomer, and the right figure is the H NMR spectrum of dimer. It can be seen from the figure that the chemical shifts 5.40, 4.60, and 4.66 ppm are the characteristic peaks of methylene on the oxazine ring N-CH2-Ar and -O-CH2-N; 2.29 ppm is the characteristic peak of -CH3. After 365 nm ultraviolet irradiation for 30 minutes, the characteristic peaks of the oxazine ring are still there, indicating that the oxazine ring is not destroyed, but two new absorption characteristic peaks belonging to cyclobutane are generated at 4.58 and 4.19 ppm, and a new photodimer is synthesized.
[0048] Figure 2 The infrared spectra are shown in Figure 1. The left figure is the infrared spectrum of benzoxazine monomer, and the right figure is the infrared spectrum of dimer. It can be seen from the figure that 940cm -1 , 1038 cm -1and 1234 cm -1 The characteristic absorption peak of benzoxazine ring is at 940cm -1 The peaks are characteristic of the out-of-plane vibration of the benzoxazine ring; 1038 and 1234 cm -1 Symmetric and antisymmetric stretching vibration peaks of COC of benzoxazine ring; 1369cm -1 It is the characteristic peak of CN; 2916cm -1 The asymmetric stretching vibration of CH in the CH3 group is 1425 cm -1 It is the asymmetric and symmetric bending vibration of CH in CH3 group; 1613cm -1 and 1633cm -1 They are the characteristic peaks of C=C and C=O, 3446cm -1 It is the characteristic peak of -OH. After 365 nm ultraviolet irradiation for 30 minutes, 2800-2900cm -1 The characteristic peaks belonging to cyclobutane appeared, and the new photodimer was successfully synthesized.
[0049] Figure 3 It is a DSC curve diagram, the solid line is the direct heat-cured sample, and the dot-dashed line is the sample after dimerization and heat curing. It can be seen from the figure that the exothermic peak temperature of benzoxazine monomer curing is 196°C, and the exothermic peak temperature of the adhesive prepared after DSC curing after 365 nm ultraviolet irradiation for 30 minutes is 185°C.
[0050] Figure 4 Figure 2 is the TGA curve of the resin material after direct curing and photodimerization followed by thermal curing. The solid line is the direct curing sample, and the dotted line is the sample after dimerization and thermal curing. It can be seen that the temperature of the adhesive obtained by direct thermal curing of benzoxazine when it loses 5% weight is 365°C, and the residual carbon rate at 800°C is 68%; the temperature of the adhesive obtained by photodimerization followed by thermal curing when it loses 5% weight is 379°C, and the residual carbon rate at 800°C is 69%.
[0051] Figure 5 The photodimerized and heat-cured resin adhesive material has a bonding area of 1cm -2 The tensile shear strength test diagram shows that the bonding strength is 6.88MPa. The bonding strength formula is P=F / s, where F is the maximum force required for the sample to be completely separated; S is the bonding area of the sample.
[0052] Example 2
[0053] The amine source compound p-methylaniline in Example 1 was replaced by aniline. The other steps were the same as those in Example 1.
[0054] The specific chemical structural formula of aniline is: , the amount of reactants was changed to: weigh 2.56 g (0.01 mol) of isoliquiritigenin, 1.86 g (0.02 mol) of aniline, and 1.32 g (0.044 mol) of paraformaldehyde, with a yield of 80%. In this embodiment, the structure of the precursor benzoxazine monomer product obtained is:
[0055] .
[0056] The reaction formula of its thermal curing crosslinking is as follows:
[0057] .
[0058] The latent curing benzoxazine resin monomer obtained in this embodiment has a curing exothermic peak temperature of 195°C, a temperature of 372°C when benzoxazine loses 5% weight by direct thermal curing, and a carbon residue rate of 69% at 800°C; the temperature of 389°C when the weight loss is 5% after photodimerization and thermal curing, and a carbon residue rate of 71% at 800°C in an inert gas atmosphere, and its bonding strength is 6.41MPa.
[0059] Example 3
[0060] The amine source compound p-methylaniline in Example 1 was replaced by 3-ethynylaniline. The other steps were the same as those in Example 1.
[0061] The specific chemical structure of 3-ethynylaniline is , the amount of reactants was changed to: weigh 2.56 g (0.01 mol) of isoliquiritigenin, 2.34 g (0.02 mol) of 3-ethynylaniline, and 1.32 g (0.044 mol) of paraformaldehyde. The yield was 80%. In this embodiment, the structure of the precursor benzoxazine monomer product obtained was:
[0062] .
[0063] The curing and cross-linking reaction formula is as follows:
[0064] .
[0065] The latent curing benzoxazine resin monomer obtained in this embodiment has a curing exothermic peak temperature of 187°C, a temperature of 382°C when benzoxazine loses 5% weight by direct thermal curing, and a carbon residue rate of 71% at 800°C; the temperature of 391°C when the weight loss is 5% after photodimerization and then thermal curing, and a carbon residue rate of 74% at 800°C in an inert gas atmosphere, and its bonding strength is 6.92MPa.
[0066] Example 4
[0067] The amine source compound p-methylaniline in Example 1 was replaced by 2-furanmethylamine. The other steps were the same as those in Example 1.
[0068] The specific chemical structural formula of 2-furanmethylamine is: , the amount of reactants was changed to: weigh 2.56 g (0.01 mol) of isoliquiritigenin, 1.94 g (0.02 mol) of 2-furanmethylamine, and 1.32 g (0.044 mol) of paraformaldehyde, with a yield of 81%. In this embodiment, the structure of the precursor benzoxazine monomer product obtained is:
[0069] .
[0070] The reaction formula of its thermal curing crosslinking is as follows:
[0071] ,
[0072] The latent curing benzoxazine resin monomer obtained in this embodiment has a curing exothermic peak temperature of 189°C, a temperature of 5% weight loss of benzoxazine by direct thermal curing is 384°C, and a carbon residue rate of 73% at 800°C; a temperature of 5% weight loss after photodimerization and subsequent thermal curing is 398°C, and a carbon residue rate of 75% at 800°C in an inert gas atmosphere, and its bonding strength is 6.92MPa.
[0073] Comparative Example 1
[0074] Comparative Example 1 adopts the same preparation method as Example 1, except that the amount of isoliquiritigenin is changed to 0.005 mol, and the obtained benzoxazine resin monomer has a curing exothermic peak temperature of 185°C, a photodimerization, and a temperature of 294°C when the weight loss is 5% after thermal curing, a residual carbon rate of 50% at 800°C in an inert gas atmosphere, and a bonding strength of 3.62 MPa.
[0075] Comparative Example 2
[0076] Comparative Example 2 adopts the same preparation method as Example 1, except that the amount of isoliquiritigenin is changed to 0.015 mol, and the obtained benzoxazine resin monomer has a curing exothermic peak temperature of 183°C, a photodimerization, and a thermal curing temperature of 302°C when the weight loss is 5%, a residual carbon rate of 53% at 800°C in an inert gas atmosphere, and a bonding strength of 3.78 MPa.
[0077] In addition, isoliquiritigenin is very important in the monomer synthesis of the present invention. It can be seen from the above comparative examples that too high or too low a content thereof will result in a significant decrease in the bonding performance and thermal properties of the benzoxazine resin adhesive.
Claims
1. A bio-based benzoxazine adhesive, characterized in that: The structure of the resin precursor benzoxazine monomer of the adhesive is as follows: ; Among them, the Select any one of the following structural fragments: ; The preparation method of the bio-based benzoxazine adhesive comprises the following steps: mixing isoliquiritigenin, an amine compound and polyformaldehyde, adding an organic solvent, heating for reaction, removing the organic solvent by rotary evaporation, washing with water after the reaction, and drying to obtain a solid product, a benzoxazine resin precursor based on isoliquiritigenin bio-based, and then obtaining a polybenzoxazine resin adhesive by ultraviolet light dimerization and thermal curing cross-linking; The amine compound has a structural formula of R-NH2, and is selected from any one of the following structures: ; The molar ratio of isoliquiritigenin, amine compound and paraformaldehyde is 1:2:4-5; The bonding strength of the bio-based benzoxazine adhesive is above 6.41 MPa.
2. A method for preparing the bio-based benzoxazine adhesive according to claim 1, characterized in that: The following steps are involved: After mixing isoliquiritigenin, amine compounds and polyformaldehyde, an organic solvent is added, heated to react, and then the organic solvent is removed by rotary evaporation. After the reaction, the solid product is washed with water and dried to obtain a solid product based on isoliquiritigenin bio-based benzoxazine resin precursor, and then a polybenzoxazine resin adhesive is obtained by ultraviolet light dimerization and thermal curing cross-linking.
3. The method for preparing the bio-based benzoxazine adhesive according to claim 2, characterized in that: The amine compound has a structural formula of R-NH2, and is selected from any one of the following structures: 。 4. The method for preparing the bio-based benzoxazine adhesive according to claim 2, characterized in that: The molar ratio of the isoliquiritigenin, the amine compound and the paraformaldehyde is 1:2:4-5.
5. The method for preparing the bio-based benzoxazine adhesive according to claim 2, characterized in that: The molar ratio of the isoliquiritigenin, the amine compound and the paraformaldehyde is 1:2:4.
4.
6. The method for preparing the bio-based benzoxazine adhesive according to claim 2, characterized in that: The reaction temperature is 80-120° C. and the reaction time is 8-18 hours.
7. The method for preparing the bio-based benzoxazine adhesive according to claim 2, characterized in that: The reaction temperature is 100-120° C., and the reaction time is 8-12 hours.
8. The method for preparing the bio-based benzoxazine adhesive according to claim 2, characterized in that: The organic solvent is one of 1,4-dioxane, toluene and xylene or a mixture of several of them.
9. The method for preparing the bio-based benzoxazine adhesive according to claim 2, characterized in that: The isoliquiritigenin bio-based benzoxazine resin precursor can undergo photodimerization under 365 nm ultraviolet irradiation.
10. An application of the bio-based benzoxazine adhesive according to claim 1 in aerospace, hydrophobic flame retardant, anticorrosion and antibacterial, and electronic communications.
Citation Information
Patent Citations
Benzoxazine resin based on apigenin biology base and preparation method thereof
CN110951018A
Full-bio-based benzoxazine resin and preparation method thereof
CN111205420A